أثر إدارة المخاطر على تحسين أداء شركات التأمين- دراسة حالة - - بوداود, خليد (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى معرفة دور إدارة المخاطر في تحسين أداء شركات التأمين، و ذلك لما تلعبه من دور هام في تحديد الخطر الذي يمكن أن يؤثر على تحقيق الأهداف وتحليلها وتقييمها ومعالجتها ورصدها على نحو مهيكل. وجب على شركات التأمين التنبؤ بالمخاطر التي تتعرض لها و المحيطة بها و التعرف على مخلفاتها، نظرا للبيئة المتقلبة التي تنشط فيها المتضمنة لمجوعة من المعيقات ما يجعلها تواجه مخاطر قد تكون سببا في فشلها و ضعف أدائها. This study aims to know the role of risk management in improving the performance of insurance companies, due to the important role it plays in determining the risk that can affect achieving goals analyzing, evaluating, treating and monitoring them in a structured manner. Insurance companies must predict the risk they are exposed to and surrounding them and identify their waste, given the volatile environment in which they operate, including a set of obstacles, which causes them to face risks that may be the cause of their failure and poor performance
THE IMPACT OF RISK MANAGEMENT ON IMPROVING THE PERFORMANCE OF INSURANCE COMPANIES-CASE STUDY.
مقال
Keywords: شركات التأمين، إدارة المخاطر، الأداء.